Concomitant percutaneous coronary intervention and transcatheter aortic valve replacement for aortic stenosis complicated with acute STEMI: a case report and literature review - Xu, Chengyi; Hu, Hanhua; Su, Xi (Frontiers in Cardiovascular Medicine, 2023)
Aortic stenosis (AS) complicated with acute ST-segment elevation myocardial infarction (STEMI) is a life-threatening emergency with high mortality.A 75-year-old male patient attended the emergency department of Wuhan Aisa Heart Hospital in December 2021, with chest pain for 2 days and exacerbation for 1 hour. The electrocardiogram (ECG) indicated atrial fibrillation with rapid ventricular response and ST-segment depression. Echocardiography showed severe AS and mild/moderate aortic insufficiency. The patient refused coronary arteriongraphy and further invasive procedure, and then,requested discharge,, but he had recurrent chest pain in the third day.The ECG showed STEMI in extensive anterior wall. During preoperative preparation, he suffered from cardiogenic shock (CS). Concomitant percutaneous coronary intervention (PCI) and transcatheter aortic valve replacement (TAVR) was performed, but he died of CS and multiple organ failure four days after surgery. Patients with AS and STEMI might be susceptible to CS during perioperative period of concomitant PCI and TAVR, which requires proactive prevention.